Glucose uptake in Trypanosoma vivax and molecular characterization of its transporter gene - Waitumbi, J.N.; Tetaud, E.; Baltz, T. (Wiley, 1996)
A gene, TvHT1, encoding a glucose transporter protein, has been cloned from the haemoflagellate protozoon, Trypanosoma vivax, which has an active Kreb's cycle in the mammalian stage. The deduced polypeptide is similar in amino acid sequence to other kinetoplastid hexose transporters from Trypanosoma brucei (THT1 and THT2), Trypanosoma cruzi (TcrHT1) and Leishmania (Pro-1). The similarity is higher with THT2 (expressed in T. brucei insect forms) than with the other isoforms. The kientic properties of glucose uptake in Chinese Hamster Ovary (CHO) cells expressing TvHT1 and in trypanosomes show a saturable transport mechanism typical of a facilitated crrier system, with a similar affinity for d-glucose as that of the T. brucei bloodstream from carrier, THT1 (Km=0.548 + 0.01 mM, V max = 4.26+0.12 nmol min-1. mg protein-1 in CHO cells and Km=0.585+0.068 mM, V max = 88.5+6.2 nmol min-1. in T. vivax). The specificity of the TvHT1 protein for various D-glucose analogues, as judged by inhibition of 2-deoxy D-arabinose-hexose transport, shows properties that are intermediate between those ofTHT1 on the one hand and TcrHT1 and THT2 on the other. As with the hexose transporters in the other members of Kinetoplastida, the TvHT1-encoded system differs from erythrocyte-type glucose transport by its moderte sensitivity to cytochalasin B and its capacity to transport fructose.